Prevalence of Urinary Tract Infection and Associated Effective Factors During Pregnancy in Shahrekord, Iran - Mehri Rejali; Seyede Soghra Ahmadi (Shahrekord University of Medical Sciences, 2018)
Background and aims: This study was conducted to determine the prevalence of urinary tract infection (UTI) in the pregnant women and the associated risk factors in Shahrekord, Iran. Methods: In this cross-sectional study, 832 pregnant women were examined up to 26 to 30 weeks of pregnancy and their UTIs were studied. The required information was collected by examining the health records of pregnant women and completion of the data registration forms. All statistical analyses were performed in SPSS 23.0 using chi-square and independent t test. Results: According to the results of this study on 832 participants, 109 of them were diagnosed with UTI, and prevalence of UTI was recorded to be 13.1% in this study. There was a significant relationship between urinary infection and variables of delivery, pregnancy severe vomiting, genitourinary problems, infertility, and blood group. Conclusion: According to the results of this study, screening and treatment of UTIs have been on time and appropriate in health systems of Shahrekord city which have led to the reduction of infant and maternal diseases. Even in the conditions that there is no UTI, continuing the process for screening and treatment is recommended.